Russia and China A political marriage of convenience - stable and successful - Lubina, Michal (Verlag Barbara Budrich, 2017)
This book depicts the sophisticated relationship between Russia and China as a pragmatic one, a political marriage of convenience. Yet at the same time the relationship is stable, and will remain so. After all, bilateral relations are usually based on pragmatic interests and the pursuit of these interests is the very essence of foreign policy. And, as often happens in life, the most long-lasting marriages are those based on convenience. The highly complex, complicated, ambiguous and yet, indeed, successful relationship between Russia and China throughout the past 25 years is difficult to grasp theoretically. Russian and Chinese elites are hard-core realists in their foreign policies, and the neorealist school in international relations seems to be the most adequate one to research Sino-Russian relations.